The cranial morphology of Rhyacotriton olympicus olympicus (Gaige) - Cloete, Stephanie E (Stellenbosch : Stellenbosch University, 2012)
Also published in: Annale. Universiteit van Stellenbosch. Serie A, vol. 36, nr. 2, 1961.